2018
DOI: 10.4315/0362-028x.jfp-17-420
|View full text |Cite
|
Sign up to set email alerts
|

Transfer and Redistribution of Salmonella Typhimurium LT2 and Escherichia coli O157:H7 during Pilot-Scale Processing of Baby Spinach, Cilantro, and Romaine Lettuce

Abstract: Several outbreaks of foodborne illness traced to leafy greens and culinary herbs have been hypothesized to involve cross-contamination during washing and processing. This study aimed to assess the redistribution of Salmonella Typhimurium LT2 during pilot-scale production of baby spinach and cilantro and redistribution of Escherichia coli O157:H7 during pilot-scale production of romaine lettuce. Four inoculated surrogate:uninoculated product weight ratios (10:100, 5:100, 1:100, and 0.5:100) and three inoculatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…Antimicrobial treatments, nonetheless, reduced pathogens on treated samples, with geraniol-using treatments (GPN, UG) being more effective for reducing pathogen numbers as compared to HOCl and Control treatments. While the potential for multiple crosscontamination events should be low for produce packed and held in a sanitary environment, research has demonstrated the opportunity for post-harvest contamination of pathogens to occur even when sanitizing treatments are applied (Pao et al, 2012;Singh et al, 2018;Smolinski et al, 2018). This occurrence is one the FDA's final rule on produce safety aims to prevent by the mandatory application of food safety hazard reduction strategies (FDA, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antimicrobial treatments, nonetheless, reduced pathogens on treated samples, with geraniol-using treatments (GPN, UG) being more effective for reducing pathogen numbers as compared to HOCl and Control treatments. While the potential for multiple crosscontamination events should be low for produce packed and held in a sanitary environment, research has demonstrated the opportunity for post-harvest contamination of pathogens to occur even when sanitizing treatments are applied (Pao et al, 2012;Singh et al, 2018;Smolinski et al, 2018). This occurrence is one the FDA's final rule on produce safety aims to prevent by the mandatory application of food safety hazard reduction strategies (FDA, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Organisms were selected to accommodate biosafety needs for already published research conducted simultaneous to data collection in the current study (Yegin et al, 2016). Previous research has indicated these and other similar virulence-attenuated organisms functioned effectively as pathogen surrogates for evaluating decontamination of stone fruit (Yun et al, 2013), or have demonstrated utility for discerning pathogen spread during leafy vegetable packing in research pilot facilities (Smolinski et al, 2018).…”
Section: Preparation Of Microorganisms For Inoculation Onto Spinach Sample Surfacesmentioning
confidence: 99%
“…To ensure a minimum free chlorine level in wash water, it may be necessary to increase the average free chlorine level during washing above the minimum to replenish free chlorine loss due to natural decay and depletion. In the FDA-LGRAM, washing parameter X S, which represents the fraction of pathogens remaining on lettuce pieces during washing, was estimated based on the study published by Smolinski et al (2018), which was not specific to E. coli O157:H7 on lettuce (but rather for Salmonella on lettuce and E. coli O157:H7 on radicchio). As data become available on the proportion of E. coli O157:H7 remaining on lettuce pieces during washing, the model can be updated accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…had minimal impact on the final results. Using the same processing line design as the one discussed in Buchholz et al ., we also used data generated by Smolinski et al . on spread of E. coli O157:H7 during flume washing and drying of fresh‐cut romaine lettuce to calibrate the pathogen binding rate ( β LW ) in Equations and (data and results not shown here).…”
Section: Methodsmentioning
confidence: 99%